Catcalling As A Form Of Verbal Abuse: Psychological Impact On Women In Public Spaces From The Perspective Of Law And Human Rights - Oktavia, Putri; Fahrian, Yudi; Sasi, Kartika (JURNAL HUKUM SEHASEN, 2025)
This study examines verbal harassment (catcalling) as a form of sexual violence that violates moral norms and creates feelings of discomfort and threat for victims. Article 5 of Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence regulates harassment, but does not explicitly include catcalling as verbal harassment. This study uses normative legal methods with a focus on analyzing legal rules and concepts. The results indicate that the implementation of Article 5 has not been optimal due to a gap between what should apply (das sollen) and the reality that occurs (das sein). The main obstacles include legal difficulties in proving the case, ineffective inter-agency coordination, and sociological factors such as stigma and victims' fear of reporting. To overcome these obstacles, clearer implementation guidelines, gender-sensitive training for law enforcement officers, victim- friendly reporting procedures, and increased public legal awareness are needed.